Policing problem places: crime hot spots and effective prevention - Braga, Anthony Allan (Studies in crime and public policy, 2010)
Introduction -- The emergence of hot spots policing -- The theoretical importance of place in crime prevention -- The empirical evidence for hot spots policing -- Dealing with problem places -- Enhancing police legitimacy through community engagement -- In problem places -- Conclusion : improving policing by focusing on problem places